Toughened carbon-fiber reinforced epoxy via isophorone diisocyanate amine surface modification. (16th March 2020) - Attard, Thomas L.
Abstract: Surface modification of a c arbon-f iber reinforced e poxy (CF/E) via i sophorone d iisocyanate a mine (IDA) is investigated. The covalently bonded IDA, engendering a microscopically thin layer (2 μm–50 μm wide), is an exchange chemical reaction after topically spraying polyurea moieties (isocyanate and amine groups) to curing epoxy that is composed of amine and epoxide groups reacting for t c hours (h). Quasi-static nanoindentation, uniaxial tension and uniaxial compression tests reveal that the chemical bond feature of the tunable IDA surface, conceived at low t c, markedly improves damage tolerance in brittle CF/E by significantly supplementing the energy-release rate (fracture toughness). Compression tests revealed that energy absorption and deflection ductility of IDA-modified CF/E, i.e., C-IDA, and prepared at t c = 0 h, are two and five times greater relative to C-IDA at t c = 0.5 h. Tension tests revealed that energy absorption and deflection ductility of C-IDA at t c = 0 h are 150% and 50% greater than C-IDA at t c = 24 h. Micromechanical properties of the IDA reaction include a uniquely distributed reduced elastic modulus ( E r ), bounded by moduli of pure epoxy and pure polyurea (overspray). The results, in concert with atomic force microscopy (AFM) and non-negative matrix factorization (NMF) results, validate a link between IDA chemistry and mechanical energy transferability. Manifested as damage localization, fractograph analysis also confirms existence of the link, where bridging of individual damage events in CF/E is markedly reduced. Graphical abstract: Image 1 Highlights: Fractograph analysis confirms marked reduction of bridging of individual damage. IDA topographies indicate distribution patterns of reduced elastic modulus Er (tc). Large Er indicate quality IDA, helping to sustain high-strength of carbon-fiber. Nonlinear model confirms tremendous C-IDA fracture toughness and ductility.